Activation of disease resistance against Botryosphaeria dothidea by downregulating the expression of MdSYP121 in apple. Issue 1 (1st May 2018) - He, Xiaowen; Huo, Yanhong; Liu, Xiuxia; Zhou, Qianqian; Feng, Shouqian; Shen, Xiang; Li, Baohua; Wu, Shujing; Chen, Xuesen
Abstract: In plants, the vesicle fusion process plays a vital role in pathogen defence. However, the importance of the vesicle fusion process in apple ring rot has not been studied. Here, we isolated and characterised the apple syntaxin gene MdSYP121 . Silencing the MdSYP121 gene in transgenic apple calli increased tolerance to Botryosphaeria dothidea infection; this increased tolerance was correlated with salicylic acid (SA) synthesis-related and signalling-related gene transcription. In contrast, overexpressing MdSYP121 in apple calli resulted in the opposite phenotypes. In addition, the results of RNA sequencing (RNA-Seq) and quantitative real-time PCR (qRT-PCR) assays suggested that MdSYP121 plays an important role in responses to oxidation–reduction reactions. Silencing MdSYP121 in apple calli enhanced the expression levels of reactive oxygen species (ROS)-related genes and the activity of ROS-related enzymes. The enhanced defence response status in MdSYP121-RNAi lines suggests that syntaxins are involved in the defence response to B. dothidea . More importantly, we showed that MdSYP121 forms a soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complex with MdSNAP33, and the complex may participate in regulating resistance to B. dothidea . In conclusion, by regulating the interaction of SA pathway and oxidation–reduction process, MdSYP121 can influence the pathogen infection process in apple. Plant defense: Regulating resistance to ring rot: A gene with multiple functions in defense against apple ring rot may provide a target for breeding apple varieties resistant to this devastating and enigmatic fungal disease. In China, the world's greatest producer of apples, apple ring rot poses a severe challenge to growers. A Chinese team led by Shujing Wu and Xuesen Chen, of Shandong Agricultural University, explored the role of a gene, MdSYP121, thought to provide resistance to ring rot. A combination of genetic, genomic, and transgenic experiments showed that MdSYP121 does indeed confer resistance to the disease, and may do this both by regulating hormonal pathways of defense and by stimulating enzymes involved in defensive oxidation/reduction reactions. Overall, their results suggest potential foci for breeding programmes aimed at reducing the susceptibility of apple cultivars to the ring rot fungus.